Properties of Ta2O5 thin films prepared by ion-assisted deposition - Farhan, M.S.; Zalnezhad, E.; Bushroa, A.R. (Elsevier, 2013)
Tantalum penta-oxide (Ta2O5) thin films were deposited onto highly polished and clean, fused silica glass substrates via ion beam-assisted deposition at room temperature using a high-vacuum coater equipped with an electron beam gun. The effects of ion beam parameters, oxygen flow rate, and deposition rate on the optical and structural properties as well as the stress of Ta2O5 films were studied. It has been revealed that Ta2O5 thin films deposited at 300 eV ion beam energy, 60 μA/cm2 ion current density, 20 sccm oxygen flow rate and 0.6 nm/s deposition rate demonstrated excellent optical, structural and compressive stress.